2021
DOI: 10.1007/s11187-021-00531-3
|View full text |Cite
|
Sign up to set email alerts
|

Narratives in entrepreneurial ecosystems: drivers of effectuation versus causation

Abstract: This paper introduces narratives in entrepreneurial ecosystems as drivers of effectuation vs. causation. Drawing on 43 interviews with successful players in Silicon Valley, Munich, and Singapore, we found ecosystem-specific narratives indicate what is common, appropriate, and successful in each ecosystem, and these narratives encourage either effectuation or causation. Our findings indicate that the narratives in the ecosystem in Silicon Valley facilitate effectuation, in Munich causation, and in Singapore a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 93 publications
1
6
0
1
Order By: Relevance
“…This is consistent with recent suggestions that effectual and causation activities are not mutually exclusive (Berends et al, 2014;Reymen et al, 2015). Our work is in line with recent research by Hubner et al (2021), which has shown that different factors will strengthen or on the contrary counterbalance each other in a complementary logic of effectuation and causation. Effectuation represents exploration in the face of uncertainty.…”
Section: Appropriationsupporting
confidence: 94%
“…This is consistent with recent suggestions that effectual and causation activities are not mutually exclusive (Berends et al, 2014;Reymen et al, 2015). Our work is in line with recent research by Hubner et al (2021), which has shown that different factors will strengthen or on the contrary counterbalance each other in a complementary logic of effectuation and causation. Effectuation represents exploration in the face of uncertainty.…”
Section: Appropriationsupporting
confidence: 94%
“…An overview of the papers addressing the interdependencies within ecosystems is presented in Table 1. 5 The dynamics within ecosystems are driven by feedback and non-linear co-evolution between ecosystem elements and the wider socio-economic-historical context (e.g., Bessagnet, Crespo & Vicente, 2021;Bischoff, 2019;Daniel et al, 2022;Eichelberger et al, 2020;Grande et al, 2022;Hubner et al, 2022;Marinelli et al, 2022;Yamamura & Lassalle, 2020). By extension, this means that ecosystems are unique due to their co-evolving elements and historical, cultural, and institutional heritage (Mack & Mayer, 2016) and their configuration and the resulting feedback effects can vary significantly (Spigel, 2017).…”
Section: Interdependencies Within Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…News is a linguistic statement of facts, so facts are primary, followed by reports ( Francesco et al, 2020 ). No matter how media technology evolves, the essence of news remains to be reporting on recent facts ( Hubner et al, 2021 ). The value elements of news are still critical criteria for people to measure the value of a news release, namely, the authenticity, timeliness, essentiality, distinction, proximity, and attractiveness of news ( Miho, 2020 ).…”
Section: Related Theories Research Hypotheses and Research Modelmentioning
confidence: 99%